Role of Cystatin-C as Serum Biomarkers in Predicting Glomerular Function-Associated with Copper-Induced Acute Kidney Injury (Majalah Kedokteran Bandung, 2020)
Cystatin C is a 13 kD molecular-weight protein synthesized by all nucleated cells which functions as a cysteine protease inhibitor. Cystatin C is detectable when kidney function decreases due to the excessive accumulation of nephrotoxic substances such as copper. Previous studies have proven that white turmeric rhizome can act as a nephroprotector agent at a dose of 500mg/BW. The purpose of this study was to compare Cystatin-C marker and serum creatinine as biomarkers in the examination of acute kidney injuries induced by nephrotoxic substance. This was a post-test only controlled experimental study on wistar strain male rats that were divided randomly using simple random sampling approach into three groups: normal control group, treatment control group (Curcumin for 2 weeks followed by CuSO4 for 3 days at each weekend), and CuSO4 pentahydrate control group. This study was conducted in Faculty of Pharmacy and Faculty of Medicine of the University of North Sumatera in May to August 2019. Results were normally distributed with significant differences in levels of Cystatin-C, creatinine, and protein serum due to differences in the treatment of each group  (p
Keywords: Copper; Cystatin-C; Nephroprotector; Nephrotoxic; White Turmeric